The Effect of Psychological Capital Level of Employees on Workplace Stress and Employee Turnover Intention (2018)
There have been ongoing debates on ways to manage occupational stress. One of the most important debates is on how to increase employees’ resistance level against stress. The purpose of this research is to examine the effects of psychological capital on workplace stress and turnover intention, and to reveal the mediation of workplace stress on the relationship between the psychological capital level of employees and turnover intention. Research was conducted on 719 employees of the tourism sector in Antalya (Turkey), thought to be under great stress due to the intense interaction with customers. In this context, confirmatory factor analysis was made in order to test whether the adapted scales were appropriate for research data. Hypotheses and the effect of mediation were tested through hierarchical regression. The results proved that psychological capital has a negative and significant effect on workplace stress and employee turnover intention. Furthermore, research outcomes showed that workplace stress partially mediates the effect of psychological capital on turnover intention. Practitioners of the tourism sector were advised about the importance of psychological capital, which can be improved by training, in terms of finding solutions to job stress and turnover rate.